Developing Critical Thinking in Psychology: The Role of Cognitive Processes in Problem-Solving and Decision-Making - Arfa Akram; Mushahed Nawaz; Sundas Sattar; Ayesha Tasawar; Shaista Ajmal; Awais Ur Rahman (Research Journal of Psychology, 2024)
This research aims in understanding of cognitive processes in development of critical thinking whereby special focus is accorded to problem solving and decision making in the course of psychological study. Regarding quantitative data, we administered a structured questionnaire on 150 students of psychology course. It emerged that critical thinking, problem solving, and decision making enjoy a very high level of association with one another and that critical thinking predicted the two other skills significantly. Critical thinking score has direct relationship with over all problem solving ability, decision making ability etc with in the study participants. Therefore, one high-impact area highlighted by our work is to incorporate specific practice sessions that enhance these executive functions into psychology education. The findings presented within this research may be useful for better understanding cognitive development and its importance for current and future academic and occupational achievements.